Utilizing the topology of configuration space in real-time manipulator path planning - Fox, John J., author; Maciejewski, Anthony A., author; IEEE, publisher (Colorado State University. Libraries, 1994)
This paper provides a set of algorithms which allow qualitative information regarding the connectivity of configuration space to be quickly established. A mechanism is presented which utilizes these results to determine the effects of the motions of one manipulator on the configuration space of the other. These algorithms are then used as a basis for a simple planner which is capable of rapidly computing collision free paths for multiple SCARA manipulators operating within overlapping workspaces.